Entropy-Based Study of Components in Open-Source Software Ecosystems - Yu, Liguo; Cawley, John; Ramaswamy, Srini (INFOCOMP Journal of Computer Science, 2012)
Open-source software productis contain free components that can be used by both individuals and companies. When open-source commercial off the shelf (COTS) components become integral parts of a commercial product, the open-source project and the comercial software organizations tend to form relationship akin to an ecosystem. In this paper, we apply entropy to measure the diversity of an open-source ecosystem, in which it represents and measures the attractiveness of open-source components. We studied 121 Eclipse products to understand their evolution. Our study finds that although most of the Eclipse products’ popularity increase over time, their representative product, the Java IDE´s popularity has remained relatively stable in recent years.